LHC High-β∗ Runs: Transport and Unfolding Methods. (25th September 2012) - Trzebiński, M.; Staszewski, R.; Chwastowski, J.
Abstract : The paper describes the transport of the elastically and diffractively scattered protons in the proton-proton interactions at the LHC for the high-β ∗ runs. A parametrisation of the scattered proton transport through the LHC magnetic lattice is presented. The accuracy of the unfolding of the kinematic variables of the scattered protons is discussed.